Evaluation of Functional Fat from Interesterified Blends of Butter Oil and Moringa oleifera Oil - Nadeem, Muhammad; Abdullah, Muhammad; Javid, Arshad; Arif, Atta Muhammad; Mahmood, Tariq (Pakistan Journal of Nutrition, 2012)
The main objective of this research work was to develop a functional fat from Butter Oil (BO) and Moringa oleifera Oil (MOO) blends by interesterification process. To prevent the separation of liquid and solid phase the blend was chemically interesterified. MOO was incorporated into BO at five different levels i.e. T1 (90% BO and 10% MOO) T2 (80% (BO) and 20% MOO) T3 (70% BO and 30% MOO) T4 (60% BO and 40% MOO) and T5 (50% BO and 50% MOO). All these treatments were compared with a control T0 which did not contain any addition of MOO (100% BO). Melting point of all the treatments along with control increased after interesterification. Melting point of T5 was 35.5°C with iodine value of 60.44 (g/100 grams). Cholesterol reduction with beta cylodextrin increased as the concentration of MOO increased in the blend. The cholesterol reduction in T1 and T5 was 87 and 94% respectively as compared to control 85%. Oxidative stability was significantly increased with increasing augmentation of MOO in the blend. After 5 days in oven at 63°C the peroxide value of T5 was 2.19 as compared to control 13.14 (M. Eq./kg). It can be concluded that MOO and BO can be used in the formulation of functional and shelf stable fat.